Kehamilan usia dini di wilayah kerja UPT Kesmas Tegalalang I Kabupaten Gianyar, Bali-Indonesia - Raka Mery Hardiani; Daondy Friarsa; Aswin Panji; Luh Seri Ani (Intisari Sains Medis, 2019)
Introduction: Early pregnancy events are predicted to increase globally by 2030. Early pregnancy is a global problem that occurs in countries with high, middle, and low economic status. Pregnant women aged 10-19 years are at high risk of eclampsia, puerperal endomtritis and systemic infections. This study aims to determine the description of early pregnancy at the UPT of the Primary Health Care Center Tegallalang I Gianyar-Bali.Methods: Descriptive research using cross-sectional design was carried out on 22 pregnant women in the Primary Health Care Center Tegallalang I Gianyar, Bali. The sample was selected using the total sampling method. Data collection was conducted in May 2018. Early pregnancy data along with respondent characteristics were collected by interview method. Early pregnancy is determined based on the age of adolescents when <20 years pregnant. Data were analyzed descriptively to obtain proportions and trends in the incidence of early pregnancy.Results: The prevalence of pregnancy at an early age was 13.6%. Early pregnancy is more prevalent in mothers who do not work (22.2%) and education levels are low (25%). All pregnant women early in the second trimester of pregnancy (100%), have performed ANC services and consume blood boosting tablets (Fe). In this study it was also found that one person had not received Tetanus Toksoid (TT) immunization, was in an abnormal BMI and blood pressure. There are no early pregnant women who have anemia.Conclusion: The prevalence of early pregnancy is relatively high, so primary and secondary prevention efforts need to be intensified to reduce the incidence of early pregnancy and its negative effects.